STUDI TENTANG DAMPAK PEMBELAJARAN YANG MENGINTEGRASIKAN NILAI-NILAI MORAL TERHADAP PEMBENTUKAN KATAKTER PESERTA DIDIK: (SYSTEMATIC LITERATURE REVIEW) - Dewi Sri Wahyuni; Lilies N. Tangge; Afadil (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2024)
This research is a systematic literature study (Systematic Literature Review) on the impact of learning that integrates moral values on the formation of students' character. This research uses a systematic literature review method which is a method that focuses on the stages or process of identification, study or analysis, evaluation, as well as interpreting and making conclusions based on research results contained in articles in a systematic and structured manner that follows predetermined stages so that it can used as a solution to the specified problem. It is hoped that the results of this research will provide benefits; (1) as information for teachers and lecturers to find out the impact of learning that integrates moral values on the formation of students' character. (2) as a reference for lecturers to conduct similar research and as material for reflection in correcting mistakes that have occurred.